Analysis of Vat Payment Reporting Methods for Business Partners at PT X in Gresik - Nuril Hidayah, Devita; Reviandani, Wasti (International Journal of Economics (IJEC), 2025)
This study discusses the analysis of business partner payments without VAT deductions against overpayments at Company X. The purpose of this study is to analyze the impact of payments from business partners without VAT deductions that cause overpayments to Company X and increase understanding of efficient payment practices. This research method uses descriptive qualitative research methods. Data analysis was carried out by means of interviews and observations. The results of this study indicate that the verification and VAT deduction process has not been running optimally. This is indicated by the existence of business partner payment transactions in the periode from January to June 2025 which were carried out without VAT deductions, so that It can result In overpayments where company X eceives more funds than the inovices that have been issued, this has an impact on financial eficiency